Dimensions of micro-insurance and their relationship to achieving insurance coverage / applied research in the Iraqi general insurance company - Khaleel, Omer Dawood; Lafta, Baydaa Staar (Edelweiss Applied Science and Technology, 2024)
The research aims to determine the nature relationship Link Between dimensions Microinsurance represented by (low-income groups, reasonable cost, low premium, low coverage) in the dependent variable insurance coverage with its two dimensions represented by (access, use), and the degree of arrangement of those dimensions according to their priorities, Incarnated The research problem that the researcher came up with during field visits to the researched company in the training phase, and reviewing the approved insurance programs, it was noted that the company lacks insurance programs and production plans, marketing documents that cover risks to low-income groups, and the lack of a tool that enables the insurance service to reach all segments of society. The descriptive analytical approach was adopted, and in light of it, the questionnaire was prepared as a main tool in obtaining data from the research community, which numbered (55) people who were in Levels Administrative (senior, middle, and executive) departments in the Iraqi General Insurance Company were tested with a set of appropriate statistical methods. The data was analyzed based on ready-made statistical programs (Spss v.28) to calculate (weighted arithmetic mean, standard deviation, coefficient of variation, Pearson correlation coefficient, a test z), and the research reached a set of results, the most prominent of which was: There is a positive correlation strong and moral Between the dimensions of a For micro insurance Combined and insurance coverage, Its value reached(0.815).